Development and performance evaluation of a solar powered groundnut sheller - Vinod Choudhary; Gajendra Singh; Rajendra Machavaram (Cogent Engineering)
A solar powered groundnut sheller was developed and evaluated for shelling the groundnut pods with diminished environmental pollution and cost of shelling. The developed solar powered groundnut sheller mainly consists of a shelling unit, a power transmission system, and solar energy appliances. The maximum power consumption of the sheller during shelling operation was found to be 89.12 W. The operational time of the sheller was 48 min without charging the battery. The mean shelling capacity, shelling efficiency, damaged kernels, and unshelled groundnut pods at 6.82% (db) moisture content were calculated as 131 kg/h, 88.68%, 2.2%, and 9.12%, respectively. The shelling capacity of the developed sheller was 2.6 times more than that of the manual shelling (50.9 kg/h). The energy demand obtained during the operation of shelling groundnut pods was measured to be 2.15 kJ/kg, and it can save around 7.28 kJ/kg energy demands over the manual shelling. It could be operated by a single worker with a total cost of Rs. 582.97 (7.71 USD) per ton to shell the groundnut pods. Thus, it can save almost Rs. 2091.68 (27.65 USD) per ton compared to the manual shelling of groundnut pods. It is a woman-friendly reduced human drudgery by 84% compared with the manual shelling of groundnut pods. The shelling cost of groundnut pods using the developed sheller was 78% lower than that of the existing manual sheller. Hence, it is an efficient and economical substitute for the shelling of groundnut pods for India’s small and medium sized farmers and industries.